Optimization of Electrochemical Phosphate Recovery from Industrial Sludge Residue Generated from Supercritical Water Oxidation Treatment with H2O2 - Tekbas, M.; Bektas, N. (Esg, 2018)
Hydrothermal oxidation in supercritical water (SCWO) is a unique and potential treatment technology for wastewater with high concentration of organics. In this process, oxidants and supercritical water dissolved organic molecules make inorganic compounds more soluble, thus creating ash-free inorganics from organic species at the bottom of SCWO reactor. This inorganic residue is very reactive and can easily dissolve into some inorganic chemical species in solvents. Electrocoagulation (EC) is a process that metal anode electrodes are dissolved into the electrolyte solution when electrical current passes through the electrodes. Electrochemical dissolution of aluminium (Al) anodes in EC reactor produces Al ions, which can be used to recover dissolved phosphate residue from acid solutions. In this study, electrochemically gained Al ions were used in the recovery of phosphate from SCWO residue. Process parameters such as reaction time, current density and pH were investigated using Box-Behnken design (BBD) as a Response Surface Methodology (RSM). Optimum operating conditions were evaluated, and the results showed accurate validities between the observed and predicted values.
Keywords: Supercritical water oxidation; sludge destruction; Box-Behnken design; mixed industrial sludge